Curcumin downregulates homeobox gene NKX3.1 in prostate cancer cell LNCaP - Zhang, Hui-Na; Yu, Chun-Xiao; Zhang, Peng-Ju; Chen, Wei-Wen; Jiang, An-Li; Kong, Feng; Deng, Jing-Ti; Zhang, Jian-Ye; Young, Charles Yf (Acta pharmacologica Sinica, 2007)
Aim： To elucidate the effect and the mechanisms of curcumin on the expression of the human homeobox gene NKX3.1 in the prostate cancer cell LNCaP. Methods： The expression change of NKX3.1 in cells incubated with varying concentrations of curcumin was observed by Western blotting and RT-PCR. A dual luciferase reporter assay was used to test the effect of curcumin on the activity of the NKX3.1 1040 bp promoter. Curcumin-treated cells disposed to a designated amount of androgen analog R1881 and the androgen receptor （AR） antagonist flutamide, then the expression of NKX3.1 or the activity of the NKX3.1 promoter were investigated by Western blotting or reporter gene assay, respectively. Finally, Western blotting and electrophoretic mobility shift assay were performed to demonstrate the effect of curcumin on the expression of AR and its binding activity to the androgen response element （ARE）. Results： Curcumin downregulated the expression of NKX3.1 and the activity of the NKX3.1 1040 bp promoter in LNCaP cells. R1881 increased the expression of NKX3.1, and theAR antagonist flutamide decreased the expression of NKX3.1 in LNCaP cells, while curcumin could inhibit androgen-AR mediated induction of NKX3.1 expression. Curcumin decreased the expression of AR and the binding activity toARE directly. Conclusion： Curcumin could downregulate NKX3.1 expression in LNCaP cells. It could also inhibit the androgen-AR mediated induction of NKX3.1 expression by downregulating AR expression and blocking its DNA binding activity.